2003
DOI: 10.1182/blood-2002-03-0947
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical characteristics of myelodysplastic syndrome with bone marrow eosinophilia or basophilia

Abstract: By retrospectively analyzing 288 patients with de novo myelodysplastic syndrome (MDS), we sought to determine the prevalence and clinical characteristics of bone marrow eosinophilia and basophilia that were detected at presentation. Bone marrow eosinophilia and basophilia were defined as a differential count of each cell type exceeding 5.0% and 1.0%, respectively. Of 288 patients with MDS, 36 (12.5%) fulfilled this criterion for bone marrow eosinophilia (MDS-Eos); 34 patients (11.8%) showed basophilia (MDS-Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
56
2
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 25 publications
(26 reference statements)
5
56
2
4
Order By: Relevance
“…13 Accordingly, low percentages of RARS and CMML were found in Asian countries (Table 4), 3,5,11,14 since these two subtypes mostly occur in older patients, as also shown in our series. Apart from the ethnic and demographic reason for this disparity, we believe that environmental factors, including chemical contamination and infectious agents may also play a role.…”
Section: Discussionsupporting
confidence: 49%
“…13 Accordingly, low percentages of RARS and CMML were found in Asian countries (Table 4), 3,5,11,14 since these two subtypes mostly occur in older patients, as also shown in our series. Apart from the ethnic and demographic reason for this disparity, we believe that environmental factors, including chemical contamination and infectious agents may also play a role.…”
Section: Discussionsupporting
confidence: 49%
“…Although there was no difference in the distribution of cytogenetic subgroups according to IPSS, the frequency of chromosomal abnormalities was lower in Japanese patients with RA; notably that of isolated del (5q) was lower in Japan. Toyama et al 18 and Matsushima et al 20 reported that Japanese patients with MDS had a lower frequency of isolated del (5q) than Western reports (2.0% and 1.5%, respectively). Morel et al 21 and Greenberg et al 5 reported that the frequencies of isolated del (5q) in all MDS cases were 4.7% and 5.9%, respectively.…”
Section: Discussionmentioning
confidence: 94%
“…Cytogenetic abnormalities whichhavepowerfulprognosticimpactinMDSarefoundin morethan50%ofMDSpatients [3][4][5].Severalreportscompare the chromosome abnormalities of MDS patients from Eastern and Western countries [6][7][8][9][10][11]. The most common cytogeneticaberrationforWesternersorAfricanswas-5/5q- [3,[12][13][14][15].Ontheotherhand,Lietal.…”
Section: Introductionmentioning
confidence: 99%